The genome of Plasmodium falciparum - Mitchell, David Patrick (Trinity College (Dublin, Ireland). Department of Microbiology, 2007)
The base distribution of the 14 nuclear chromsomes, of the plastid and the mitochondrion of the malarial parasite Plasmodium falciparum were studied. Isochores were discovered in the nuclear chromosomes and found to be consistently associated with the presence of erythrocyte membrane protein 1 genes. The centromeres of the nuclear chromosomes were identified by their low GC content. Base distribution within the genome was found to follow a set of mathematical laws which were subsequently found to hold in all genomes.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin